What We Should Know About Genetically Modified Foods (Journal of Science and Technology, 2016)
Most of us know very little about the way our food plants are grown and are far removed from the factories where they are processed. All we care about is that our food should be wholesome, nutritious and tasty. Critics of crop biotechnology are of the opinion that potential ecological and food safety disasters are looming on the horizon because genetically modified (GM) crops have entered the food chain. Alarmists have introduced emotionally charged terms into the debate and speak of ‘frankenfoods' and ‘genetic pollution'. Issues of food safety and food sufficiency are extremely important to the general public and all need to be adequately informed to be able to take decisions on whether or not to allow GM foods into the food chain. In this paper, I present basic facts for the general public and invite other opinions on the topic and suggestions for the Way Forward in a developing country like Ghana.